PECULIARITIES OF DEVELOPMENT OF INCLUSIVE CULTURE OF FUTURE TEACHERS OF PRESCHOOL EDUCATION INSTITUTIONS (Psychology Travelogs, 2023)
The article reveals the peculiarities of the development of inclusive culture of future preschool teachers. Proved the signs of an inclusive culture of future SEN educators as representatives of socio-economic professions include: attitude towards others, behavior and values they possess and demonstrate regarding diversity, justice and inclusion. This is characterized by their willingness to communicate with people from different backgrounds, openness to learning about different cultures and perspectives, and commitment to equality and justice. Students with a developed inclusive culture are more likely to participate in initiatives related to diversity and inclusion, enjoy discussing social justice, and actively work to overcome barriers.According to the results of the analysis of scientific sources, the inclusive culture of future preschool teachers is interpreted as an integrative quality of personality, which is manifested in a tolerant attitude towards pupils and involves recognizing the value of the differences of all children, taking into account the needs of each of them, and stimulates all participants in the educational process to cooperate and mutually assist.It is emphasized that graduates of preschool education institutions should be prepared to create an educational environment that recognizes the intellectual experience and psychological characteristics of each student, requires physical access, opportunities for optimal learning and social experience, as well as the creation of a favorable climate, and emphasizes the importance of inclusive education as a way to reduce the social exclusion of children with special needs.The study identified the components of inclusive culture of future preschool teachers: motivational and need-based, value-semantic, and behavioral and volitional. The motivational and need component includes the following characteristics: care, mutual assistance, ethical communication with a person with special educational needs. The value-sense component includes the ability to empathize, emotional response to the problems and difficulties of others. The behavioral and volitional component covers the abilities, skills and habits manifested in social communications, the stability of moral behavior, empathy.
Keywords: culture; inclusion; inclusive culture; preschool education institution; inclusive culture of future teachers of preschool education institutions